LEARNING STYLES, DEGREE CHOICE, AND CURRICULAR PROFILE IN HUMAN COMMUNICATION STUDENTS - Martínez-Flores, Fernanda Gabriela (2017)
The analysis of the learning styles of university students, considering the study program in which they are enrolled, has allowed to make some predictions regarding their academic performance. This study is aimed at identifying and establishing relationships between learning styles, the average grade obtained in high school, and the study program profile, in two cohorts of students of the Human Communication Program at the UAEM. The CHAEA Learning Styles Questionnaire was applied to 166 newly admitted students of the 2015 and 2016 cohorts who were taking the induction course for the Human Communication Study program. These students had also provided their admittance average and information on whether they had been placed on a more suitable degree program. The results reflect significant differences in learning styles in both cohorts; there are no differences between the high school average between them; in the 2016 cohort, a moderate negative correlation was found between high school average and active style: the higher the active style, the lower the average. The dominant styles in the cohorts were active and pragmatic, which corresponds to the curricular profile of the study program, where an increase of practice hours over theory hours is more significant each semester.